Síntese, caracterização e avaliação citotóxica de vidro bioativo com adição de diferentes proporções de cério - Alessandra Nogueira Santos (2014)
The literature describes experiments in which the ceria nanoparticles significantly improved the bioactive glass mensenquimais differentiation of stem cells into osteoblasts and increased production of collagen (extracellular matrix). It is not known whether this effect is observed due to the presence of nanoceria can be also observed in the presence of cerium element (Ce) in the bioactive glass network. The incorporation of Ce in bioactive glasses using the sol-gel route is the focus of this work, with the goal of developing a material for tissue engineering, with the potential to enhance osteogenesis. Bioactive glass composition based on 70S (70% SiO2-30% CaO) were produced, with the addition of cerium element, using the sol-gel route. Different ratios of Ce were introduced in bioactive glass 70S. Two thermal treatment temperatures, 700 °C and 900 °C were used. All samples passed through the milling process and then were sieved, the range of grain being used between 38 mM - 100 mM in all analyzes and tests. Analysis by X-ray diffraction (XRD), infrared spectroscopy Fourier transform (FTIR), plasma emission spectrometry (ICP-AES), images of scanning electron microscopy (SEM), X-ray spectroscopy were performed by dispersing energy (EDS), nitrogen adsorption and the Brunauer-Emmett-Teller (BET). Dynamic testing of bioactivity with time intervals of 1 day, 1 week and 4 weeks were conducted. After testing the bioactivity XRD and FTIR was performed to investigate the possible formation of the layer of hydroxyapatite (HA) in the samples. The remaining ionic solutions of bioactivity tests were also analyzed by ICP. Preliminary results were obtained showing cytotoxicity to non Cytotoxicity study. In search of more homogeneous samples, an alternative route of synthesis was also investigated in this study. Samples were produced via synthesis assisted by ultrasound and treated at 700 °C. The samples were characterized by SEM, EDS and XRD.